2003
DOI: 10.7326/0003-4819-139-5_part_1-200309020-00006
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir Disoproxil Fumarate in Nucleoside-Resistant HIV-1 Infection

Abstract: In treatment-experienced patients with suboptimal viral suppression, tenofovir DF significantly reduced HIV-1 RNA level and had a safety profile similar to that of placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(132 citation statements)
references
References 26 publications
5
125
1
1
Order By: Relevance
“…Studies demonstrating its safety and efficacy among both treatment-naive and treatment-experienced, HIV-infected adults led to its approval as part of combination antiretroviral therapy for HIV-infected adults in 2001. [4][5][6] We performed a phase I trial of a 6-day course of tenofovir DF monotherapy, followed by an individualized combination regimen that included tenofovir DF, for treatment-experienced, HIV-infected children. The toxicity and immunologic, virologic, and clinical effects of tenofovir DF as a salvage agent are reported here.…”
Section: H Ighly Active Antiretroviral Therapy (Haart)mentioning
confidence: 99%
“…Studies demonstrating its safety and efficacy among both treatment-naive and treatment-experienced, HIV-infected adults led to its approval as part of combination antiretroviral therapy for HIV-infected adults in 2001. [4][5][6] We performed a phase I trial of a 6-day course of tenofovir DF monotherapy, followed by an individualized combination regimen that included tenofovir DF, for treatment-experienced, HIV-infected children. The toxicity and immunologic, virologic, and clinical effects of tenofovir DF as a salvage agent are reported here.…”
Section: H Ighly Active Antiretroviral Therapy (Haart)mentioning
confidence: 99%
“…As a consequence of its tolerability, convenient dosing and efficacy, this nucleoside reverse transcriptase inhibitor (NRTI) has been widely used as a component of cART regimens. There are contradictory data on tenofovir-related damage: from documented damage in early reports [24][25][26][27] to a marked lack of renal toxicity in randomized placebo-controlled trials [28][29][30][31]; moreover, toxicity was found to be increased when tenofovir was given with ritonavir-boosted protease inhibitors (PI/r) compared with tenofovir given with nonnucleoside reverse transcriptase inhibitors (NNRTIs) or cART that did not include tenofovir [32]. A mechanism involving an interaction between tenofovir and PIs/r resulting in an increased risk of renal damage has been suggested [33].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a dose-and timedependent development of a Fanconi-like syndrome has been reported [5,6]. In pivotal studies assessing the safety and efficacy of TDF, renal safety profiles were found to be similar in individuals receiving and in those not receiving TDF-containing highly active antiretroviral therapy (HAART) [2][3][4]. In addition, a recent large cohort has described no significant evidence of renal dysfunction with the use of TDF in clinical practice [7].…”
mentioning
confidence: 99%